Addressing Sexual Problems in German Primary Care: A Qualitative Study - Ronja Zannoni; Elisa Dobberkau; Hanna Kaduszkiewicz; Aglaja Valentina Stirn (SAGE Publishing, 2021)
Although general practitioners (GPs) are often the first contact for patients' sexual issues, little is known about how German GPs approach, diagnose, and treat sexual problems and disorders. Therefore, the present qualitative study explores approaches and management of sexual health issues used by GPs. The sample included 16 GPs from Kiel and surroundings and Sachsen-Anhalt. The in-depth, semi-structured interviews were coded according to the qualitative content analysis by Mayring using MAXQDA. The results revealed 5 main themes, 2 of which are explored in more detail in relation to the study objective (2 and 4): (1) sexual issues that arise in general practice, (2) addressing sexuality, (3) influencing factors in doctor-patient communication about sexuality, (4) diagnosing and treating sexual dysfunctions, and (5) changes in the approach to sexuality over time. Most GPs did not routinely ask their patients about sexual problems. Common barriers included lack of time, suspected embarrassment on both sides, and fear of offending patients. Almost all GPs tended to diagnose sexual problems individually adapted to patients' issues, not following a standardized approach. Medication was offered as the main treatment for sexual problems. For complex disorders, most GPs lack sexual medicine knowledge, and they requested a better range of training courses in sexual medicine.